Thiazolothiazole-linked porous organic polymers - Zhu, Xiang; Tian, Chengcheng; Jin, Tian; Wang, Jitong; Mahurin, Shannon M.; Mei, Wenwen; Xiong, Yan; Hu, Jun; Feng, Xinliang; Liu, Honglai; Dai, Sheng (Chemical Communications, 2014)
Thiazolothiazole-linked porous organic polymers have been synthesized from a facile catalyst-free condensation reaction between aldehydes and dithiooxamide under solvothermal conditions. The resultant porous frameworks exhibit a highly selective uptake of CO2 over N2 under ambient conditions. © 2014 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20